Chicken soup for the kid's soul : 101 stories of courage, hope, and laughter - Canfield, Jack (Deerfield Beach, Fla. : Health Communications, 1998)
A collection of short stories, anecdotes, poems, and cartoons which present a positive outlook on life.
0
Keywords: Children -- Conduct of life; Children's writings; Conduct of life